Efficient Analytic Approximation of American Option Values - Barone-Adesi, Giovanni; Whaley, Robert E. (Journal of Finance, 1987)
This paper provides simple, analytic approximations for pricing exchange-traded American call and put options written on commodities and commodity futures contracts. These approximations are accurate and considerably more computationally efficient than finite-difference, binomial, or compound-option pricing methods.